2017
DOI: 10.1525/abt.2017.79.6.473
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Osmosis to Biology Students

Abstract: These standards incorporate a number of changes from the 1998 version. These changes have come about to remedy weaknesses in the standards discovered in their use by the NSTA's NCATE Program Review Board and to address concerns about the vagueness of some of the 1998 standards.In NCATE institutional reviews, the review board quickly learned that the ten standards adopted in 1998 were too broad to be addressed effectively by institutions, who interpreted the standards in many-sometimes unintended-ways. As an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…AlHarbi et al (2015) found that pre-service teachers' understanding of osmosis and diffusion concepts had a mild positive correlation with their understanding of particle theory, which suggests that greater attention needs to be invested in teaching particle theory to ensure students' understanding of diffusion and osmosis. There are some studies in which teachers more actively approached the concepts; for example, using computer animations (Reinke et al, 2021;Sung et al, 2017), exercises and experiments (Haddad & Baldo, 2010;Lankford & Friedrichsen, 2012;Odom et al, 2017), a constructivist 5E model (Artun & Costu, 2013), and concept mapping (Kose, 2007).…”
Section: Teaching About Diffusion and Osmosismentioning
confidence: 99%
“…AlHarbi et al (2015) found that pre-service teachers' understanding of osmosis and diffusion concepts had a mild positive correlation with their understanding of particle theory, which suggests that greater attention needs to be invested in teaching particle theory to ensure students' understanding of diffusion and osmosis. There are some studies in which teachers more actively approached the concepts; for example, using computer animations (Reinke et al, 2021;Sung et al, 2017), exercises and experiments (Haddad & Baldo, 2010;Lankford & Friedrichsen, 2012;Odom et al, 2017), a constructivist 5E model (Artun & Costu, 2013), and concept mapping (Kose, 2007).…”
Section: Teaching About Diffusion and Osmosismentioning
confidence: 99%
“…Regardless of which definition is used, there is pressure that drives or prevents osmosis. Osmotic pressure (Π) is described by the van’t Hoff equation (eq ), which is valid for ideal dilute solutions, and has been experimentally verified , where i is the van’t Hoff factor ( i = 1 for nonelectrolytes), M = n/V is the molar concentration of the solute in the solution, R is the universal gas constant (0.08206 L atm mol –1 K –1 ), and T is the absolute temperature. Moreover, there is a Staverman reflection coefficient, which is defined as the ratio of real to ideal osmotic pressures for a given membrane-solute combination, and this unitless reflection coefficient describes the “leakiness” of a membrane with a value varying from 0, for a membrane as permeable to the solute as to the solvent, to 1.0 for a membrane impermeable to the solute (ideal membrane). …”
Section: Principles Of Osmosismentioning
confidence: 99%
“…Teachers have used different activities and approaches to teach osmosis and diffusion, such as coin-tossing exercises to show the random processes that are central to the process ( Haddad and Baldo, 2010 ), red onions and decalcified chicken eggs to depict net water movement ( Lankford and Friedrichsen, 2012 ), and dialysis bags and potato slices to show the process on a macro scale ( Odom et al. , 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…, 2017 ). In addition, with advances in technology, there is increasing use of multimedia simulations and dynamic visualizations to complement the traditional methods used to teach osmosis and diffusion ( Rundgren and Tibell, 2009 ; Odom et al. , 2017 ; Sung et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation